Marine diatom assemblages of the Nosy Be Island coasts, NW Madagascar: species composition and biodiversity using molecular and morphological taxonomy. Issue 2 (17th February 2020) - Kryk, Adrian; BA˛k, MaŁgorzata; GÓrecka, Ewa; Riaux-Gobin, Catherine; Bemiasa, John; Bemanaja, Etienne; Li, Chunlian; DA˛Bek, PrzemysŁaw; Witkowski, Andrzej
Abstract : Madagascar is an isolated oceanic island characterized by high degrees of endemism at all taxonomic levels. The waters surrounding Madagascar are still poorly studied for benthic marine diatom assemblages. The aim of our study was to analyse the taxonomic biodiversity and molecular phylogeny of the diatom assemblages of the Nosy Be archipelago in terms of their ubiquity/rarity. A total of 65 samples from 14 sampling sites were collected from the Nosy Be and Nosy Tanikely islands in June/July 2014. Diatom identification, based on light and electron microscopic examination, revealed 332 diatom taxa. From those, ∼90 strains were isolated and successfully cultured. So far, DNA has been extracted and one chloroplast gene ( rbc L) sequenced from 21 strains in order to reconstruct their single gene phylogeny. Taxa selected for sequencing and the preliminary phylogeny are from genera considered common benthic and planktonic forms in the marine littoral: Bellerochea, Melosira, Paralia, Triceratium, Navicula, Hippodonta, Auricula, Nitzschia, Cocconeis, and some araphids. For each site, Shannon and Simpson biodiversity indices were calculated. Diatom assemblages of Nosy Be were characterized by high biodiversity. The most abundant species was Cocconeis scutellum . Whereas some of the cultured taxa seem to represent cosmopolitan or zonal forms: e.g., Bellerochea malleus, Triceratium dubium, Melosira lineata, Paralia crawfordii, or Nitzschia inconspicua, most of the taxa isolated in culture and sequenced have not been observed in earlier works based on use of molecular markers. The dominant taxa were generally those with broad geographic distribution with global/Indo-Pacific affinities. Amongst all 332 taxa, only 35% have been identified to the species level. Many of the taxa identified to the generic level may turn out to represent taxa new to science after further SEM examination and DNA sequencing.